THE EXISTENCE OF JAMU AS A TRADITIONAL DRINK IN THE PRESERVATION OF INDONESIAN CULINARY (CASE STUDY: GENERATION Z AGE 18 -23 YEARS AT TOURISM SCHOOL IN SOUTH JAKARTA) - Rano Abryanto (Asosiasi Dosen Muda Indonesia, 2024)
Jamu is a traditional Indonesian drink inherited from our ancestors. The existence of herbal medicine, which has been a culture passed down from generation to generation for a long time, is not only used as a means of treatment but can be used for other benefits such as body care or related to matters of a metaphysical nature. Little cultural information about herbal medicine has been found or conveyed. Herbal medicine is holistic, safe to consume, and has many benefits for those who regularly consume it. Two hundred respondents were involved in this research's data collection process. The family's most important role is the main factor in preserving herbal medicine. Introducing herbal medicine early will foster a concern for cultural heritage later. Apart from family, the social environment is also essential in its implementation. This research aims to determine the existence of herbal medicine among Generation Z regarding elements related to ensuring that herbal medicine remains sustainable and maintained. This research uses qualitative methods using data sources, journals, and reference documents. The data collection techniques are interviews, observation, and question and answer. The results of the research show that (1) family social culture and social environment are still relatively low, (2) sensory factors are still a feature of herbal medicine, and (3) lack of information and basic knowledge about the history of herbal medicine. jamu. (4) There are no additional subjects about herbal medicine in schools, (5) Lack of introduction of herbal medicine at the upper-class level as a treat in star hotels. (6) The current Café Jamu business model lacks a clean, hygienic, modern presentation.